Development of a sensitive competitive enzyme-linked immunosorbent assay for serodiagnosis of Burkholderia mallei, a Tier 1 select agent. - Ulrich Wernery; Elaine Chan; Rekha Raghavan; Jade L L Teng; Ginu Syriac; Sing-Yung Siu; Marina Joseph; Man-Lung Yeung; Lilong Jia; Jian-Piao Cai; Tsz-Ho Chiu; Susanna K P Lau; et al. (Public Library of Science (PLoS), 2021)
Glanders is a highly contagious and potentially serious disease caused by Burkholderia mallei, a Tier 1 select agent. In this study, we raised a monoclonal antibody (mAb) against the lipopolysaccharide (LPS) of B. mallei and developed a competitive enzyme-linked immunosorbent assay (cELISA) for B. mallei infection. Using the titrated optimal conditions of B. mallei-LPS (2 ng) for microtiter plate coating, sample serum dilution at 1:20 and 3.5 ng/μL anti-LPS mAb B5, the cutoff value of the cELISA was determined using serum samples from 136 glanders-free seronegative horses in Hong Kong. All calculated percentage inhibition (PI) values from these seronegative samples were below 39.6% inhibition (1.5 standard deviations above mean PI) and was used as the cutoff value. The diagnostic sensitivity of the developed LPS-based cELISA was first evaluated using sera from donkeys and mice inoculated with B. mallei. An increasing trend of PI values above the defined cELISA cutoff observed in the donkey and mouse sera suggested positive detection of anti-LPS antibodies. The sensitivity and specificity of the LPS-based cELISA was further evaluated using 31 serologically positive horse sera from glanders outbreaks in Bahrain and Kuwait, of which 30 were tested positive by the cELISA; and 21 seronegative horse sera and 20 seronegative donkey sera from Dubai, of which all were tested negative by the cELISA. A cELISA with high sensitivity (97.2%) and specificity (100%) for the detection of B. mallei antibodies in different animals was developed.